A physically-based constitutive model considering mixed dynamic recrystallization for a near-α titanium alloy during hot deformation - Jie Zhao; Yingming Tu; Binjun Zhou; Kehuan Wang; Gang Liu (Journal of Materials Research and Technology)
The mixed dynamic recrystallization of titanium alloys during hot deformation is rarely described in the existing microstructure evolution models and constitutive models. In this paper, the mechanism of mixed dynamic recrystallization of a near-α titanium alloy rolled sheet during hot tension was analyzed. The used TA15 rolled sheet is mainly composed of equiaxed grains with a lot of deformed structure, which promotes dynamic recrystallization during hot deformation. Continuous dynamic recrystallization is the predominant mechanism of microstructure evolution in the deformation region with the ln Z of about 47.5 and true strain of about 0.3. With the decrease of parameter Z, discontinuous dynamic recrystallization is enhanced. Then a physically-based constitutive model was developed, considering subgrain rotation, recrystallization nucleation, recrystallization grain growth, recrystallization grain transformation into deformation structure and microvoids evolution. The model can well describe the two kinds of mixed dynamic recrystallization: continuous dynamic recrystallization and discontinuous dynamic recrystallization occur successively and simultaneously. Based on the developed model, the process window of hot forming for TA15 titanium alloy components is established, realizing grain size reduction of 20 % and no necking.